FACTORS THAT INFLUENCE GOING CONCERN AUDIT OPINION ON TOURISM AND RECREATION COMPANIES DURING COVID-19 - Ruvi, Patricia Artya; Salim, Susanto (Graduate Program of Universitas Tarumanagara, 2025)
This research aims to obtain empirical evidence related to the relationship between company size, financial distress, previous year's audit opinion affects the acceptance of going concern audit opinion to tourism and recreation sub-sector companies during the covid-19 pandemic. This research uses a quantitative approach that uses secondary data. The population taken is companies engaged in the tourism and recreation sub-sector which are listed on IDX during 2020-2022. The method used in this research is logistic regression. The results of this research indicate that there is only 1 factor, namely the previous year's audit opinion, which has an influence on going concern audit opinion acceptance, while company size and financial distress have no influence. With this research, it is hoped that the company can maintain its business continuity because companies that are exposed to going concern audit opinion in the previous year tend to get it again in the following year. This is certainly not a good thing for the company to continue to get a going concern audit opinion in the following years.